2021
DOI: 10.1080/19475705.2021.1963328
|View full text |Cite
|
Sign up to set email alerts
|

Predicting susceptibility to landslides under climate change impacts in metropolitan areas of South Korea using machine learning

Abstract: To cite this article: Sang-Jin Park & Dong-kun Lee (2021) Predicting susceptibility to landslides under climate change impacts in metropolitan areas of South Korea using machine learning,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…According to the literature review, RF models perform better than other models in a variety of risk vulnerabilities than SVM and multivariate statistical analysis 25 , 47 , 48 . Most of this assessment suggested that creating several risk maps using optimal algorithm that deliver high accuracy and prediction performance of a single risk type can help to gain highly accurate information regarding relevance and interaction 38 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the literature review, RF models perform better than other models in a variety of risk vulnerabilities than SVM and multivariate statistical analysis 25 , 47 , 48 . Most of this assessment suggested that creating several risk maps using optimal algorithm that deliver high accuracy and prediction performance of a single risk type can help to gain highly accurate information regarding relevance and interaction 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study aligned with previous research where Random Forest (RF) demonstrated superior performance, employing supervised classification using spatial and geographic data, akin to findings by earlier researchers 49 51 . One of the distinguishing factors from prior studies lies in conducting spatial risk analysis of individual hazards and compound disasters through future climate scenarios 25 , 52 . Despite the inherent uncertainties of future climate scenarios, various scenarios from AR6 were employed, and the impacts based on policy scenarios were analyzed 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations